2024
DOI: 10.1590/1519-6984.250132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mannan-oligosaccharide supplementation on gut health, immunity, and production performance of broilers

Abstract: The study was designed to investigate the effect of mannan-oligosaccharide (MOS) supplementation on intestinal histomorphology, immunity against Newcastle disease virus (NDV) and productive parameters of broilers. A total of 1800, day old broiler chicks of Cobb-500 strain were selected and randomly assorted into 6 treatment groups: T1 (basal diet without antibiotics as negative control); T2 (basal diet plus antibiotics as positive control group); T3 (basal diet plus 200g/ton MOS); T4 (basal diet plus 400g/ton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
1
1
Order By: Relevance
“…Furthermore, there was a significant increase in NDV antibody titers associated with dietary Mos levels. These results were in harmony with those obtained by Asif et al (2022), who found that the supplementation of Mos significantly (P < 0.05) affected the antibody titer against NDV, where birds fed MOS showed significantly (P < 0.05) the highest antibody titer against NDV.…”
Section: Immunological Parameterssupporting
confidence: 90%
“…Furthermore, there was a significant increase in NDV antibody titers associated with dietary Mos levels. These results were in harmony with those obtained by Asif et al (2022), who found that the supplementation of Mos significantly (P < 0.05) affected the antibody titer against NDV, where birds fed MOS showed significantly (P < 0.05) the highest antibody titer against NDV.…”
Section: Immunological Parameterssupporting
confidence: 90%
“…In this study, the improvement in breast weight or percentage for group 4 may be attributed to that prebiotic has a positive effect on muscle weight including improvement of calcium, phosphorus and magnesium absorption (Cummings and Macfarlane, 2002). The present findings of intestinal parts size are in contradiction with the findings of Asif, et al (2022) who showed that MOS had significantly (P<0.05) affected the length of intestinal sections; duodenum, jejunum and ilium. Similar results were found by Padihari et al (2014) and Castillo et al (2008) they observed that addition of MOS to basal diet at a level of 0.5g/kg significantly increased the duodenum length and no effect on jejunum length as compared control group (Dimitroglou et al, 2010;Padihari et al, 2014 andChand et al, 2019).…”
Section: Carcass and Intestinal Parameterscontrasting
confidence: 84%
“…Nevertheless, the impact of yeast cell wall-based prebiotics on broiler health and performance remains a subject of debate. Some researchers have reported positive effects on performance and gut health (Pascual et al, 2020;Teng et al, 2021;Asif et al, 2024), while others found no discernible benefits (Munyaka et al, 2012;Kiros et al, 2019). Therefore, this study aims to assess the effects of using prebiotics, specifically S. cerevisiae yeast wall, both independently and in conjunction with antibiotics, on broiler performance, carcass yield, intestinal permeability, and intestinal morphometry.…”
Section: Introductionmentioning
confidence: 99%